Effect of beam energy straggling on resonant yield in thin gas targets: The cases 22Ne(p, γ)23Na and 14N(p, γ)15O. (12th July 2018) - Bemmerer, D.; Cavanna, F.; Depalo, R.; Aliotta, M.; Anders, M.; Boeltzig, A.; Broggini, C.; Bruno, C.; Caciolli, A.; Chillery, T.; Corvisiero, P.; Davinson, T.; et al.
Abstract: When deriving resonance strengths using the thick-target yield approximation, for very narrow resonances it may be necessary to take beam energy straggling into account. This applies to gas targets of a few keV width, especially if there is some additional structure in target stoichiometry or detection efficiency. The correction for this effect is shown and tested on recent studies of narrow resonances in the and reactions.